Estudo da figueira cv. roxo de valinhos no oeste potiguar - Silva, Francisco Sidene Oliveira (Universidade Federal Rural do Semi-Árido, 2018)
Studies of subtract employment in the rooting cuttings of fig tree in the semiarid conditions are still scarce, therefore, the alternative sources are a way out in the rooting cuttings of fig tree in the semiarid for the farmers. The present study aimed to evaluate the rooting cuttings, production and quality of fig tree’s fruits submitted to different managements. The research works were held in greenhouse and didactic orchard of Federal Rural University of Semiarid – UFERSA, Mossoró - RN. In experiment 1, semi-hardwood ‘Purple of Valinhos” fig tree cuttings were collected, with approximately 15 cm length. The design utilized was randomized block experiment with five treatments and four replications, being each of those constituted by six plants. The treatments were composed: soil + earthworm humus, soil + coconut fiber, soil + pollen, soil + cattle manure and soil + Tropstrato, all in proportion 1:1 (v/v). 70 days after the plantation there were evaluated the following variables: length of the aerial part, of the root and total systems of the plant, number of leaves, diameter of sprouts, root volume, chlorophyll content, dry mass of the aerial part, of the root and MSPA/MSR relation, percentage of rooted, sprouted and living cuttings. The earthworm humus’ subtract and cattle manure have promoted the largest results to all of the evaluated characteristics. In experiment 2, the use of shoot topping and the different pruning intensities (5, 10 and 15 cm) in the fig tree production, and two kinds of fructification pruning (with and without shoot topping) were evaluated. The experiments were held in factorial scheme 6x2, with four replications, being used five plants per treatment, where the three central plants were the useful area. In this action the production was evaluated during two productive cycles, in the harvests of 2016 and 2017. It was evaluated in both cycles the weight, length and diameter of the fruits, number of plant fruit-¹, and plant production-¹. The fruit quality post-crop was evaluated through the firmness, soluble solids, titratable acidity and vitamin C. The use of shoot topping and pruning intensity did not influence the physical-chemical characteristics and production of fig trees in the conditions of Potiguar West. In experiment 3, randomized blocks were performed, with six treatments and four replications, totalizing 24 parts, corresponding to different number of branches (not pruned, 6, 12, 18, 24 and 30 branches plant-¹) and four plants by part. The conduction of fig tree plants with 12, 24 and 30 branches allows a larger mass of fruits, number of fruits per plant and larger production, as well as the best chemical characteristics of fruits in the semiarid conditions. In all experiments, the variables were submitted to variance analysis and the comparing of averages was made by Tukey’s test to 5% probability
Keywords: Fruticultura; Ficus carica L.; Pós-colheita; Qualidade; Fruit farming; Ficus carica L.; Post-crop; Quality; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA